2006
DOI: 10.1530/eje.1.02113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of two different GH dosage regimens on final height, bone geometry and bone strength in GH-deficient children

Abstract: Objective: The aim was to investigate the effects of two different GH dosage regimens on growth, bone geometry and bone strength. Subjects and methods: Final height; parentally adjusted final height; the metacarpal index (MI) SDS, the inner and outer diameters; and the total cross-sectional area (CSA), cortical CSA, medullary CSA and bone strength (Bending Breaking Resistance Index (BBRI)) were evaluated at the metacarpal site in two cohorts of GH-deficient children, treated with two different doses of GH. Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…To our knowledge, there is no published randomized controlled trial on 2 GH dosages in GHD patients in which a higher GH dose is given from the start of treatment or at a young age after a few years of previous GH treatment. The study of Radetti et al [23], a nonrandomized study in which 2 groups in 2 centers were treated with doses comparable to those in our study, showed a parentally adjusted height SDS of 0.14 in the low-dose group and 0.27 in the higher-dose group; this difference was not statistically significant. A Swedish cohort from the KIGS database on a regimen of 33 µg/kg/day (approx.…”
Section: Discussionsupporting
confidence: 47%
“…To our knowledge, there is no published randomized controlled trial on 2 GH dosages in GHD patients in which a higher GH dose is given from the start of treatment or at a young age after a few years of previous GH treatment. The study of Radetti et al [23], a nonrandomized study in which 2 groups in 2 centers were treated with doses comparable to those in our study, showed a parentally adjusted height SDS of 0.14 in the low-dose group and 0.27 in the higher-dose group; this difference was not statistically significant. A Swedish cohort from the KIGS database on a regimen of 33 µg/kg/day (approx.…”
Section: Discussionsupporting
confidence: 47%
“…GH treatment is reported to increase vertebral BMD (18) and phalangeal cortical thickness (14) in children with idiopathic short stature. Data regarding the effect of GH treatment on skeletal mineralization in girls with TS include a longitudinal dose response study in Dutch girls with TS, which found increased phalangeal (mainly cortical) BMD after 7 yr of treatment, with a greater increase in the higher dose group (4).…”
Section: Discussionmentioning
confidence: 98%
“…An average ratio was also calculated as the cortical thickness divided by the total width of the metacarpal, averaged from the three locations. Additional dependent measures included Metacarpal Index (MI) and Bending Breaking Resistance Index (BBRI) (14,15). MI is calculated as (TW 2 Ϫ MW 2 /TW 2 ), and BBRI is calculated as (TW 4 ϪMW 4 /TW), where TW is total width and MW is medullary width.…”
Section: Hand Radiographymentioning
confidence: 99%
“…GH is thought to be important for optimal bone mineralization during normal pubertal development because BMD is reduced in GH‐deficient individuals and is restored with GH repletion 20 . GH treatment is reported to increase vertebral BMD 21 and phalangeal cortical thickness in children with idiopathic short stature 22 . Data regarding the effect of GH treatment on skeletal mineralization in girls with TS include a longitudinal dose–response study in Dutch girls with TS that found increased phalangeal (mainly cortical) BMD after 7 years of treatment, with a greater increase in the higher‐dose group 8 .…”
Section: Discussionmentioning
confidence: 99%